Enhanced biodegradation of a hard bis-quaternary ammonium salt - Cupková, V; Sirotková, L; Mlynarcík, D; Lacko, I; Devínsky, F (Folia microbiologica, 1992)
Bacterial strains with a high biodegradation potential were isolated from activated sludge. Their ability to decompose the hard bis-quaternary ammonium salt FB was determined by the method of chemical oxygen demand (COD) in a mineral medium, where the compound FB was the only source of carbon. The COD values were very low after 21 d and in the course of this period they reached zero level twice. The contribution of adsorption to decrease the COD value was small. The maximum COD decrease was accompanied by an increase of cell respiration. It is suggested that FB is effectively decomposed in spite of the fact that according to its structure it is a typical hard detergent.
Keywords: Biodegradation, Environmental; biodegradace; Quaternary Ammonium Compounds; Sewage; Water Microbiology; odpadní vody; mikrobiologie vody; Bacteria; kvartérní amoniové sloučeniny; spotřeba kyslíku; Oxygen Consumption